POLA PEMBINAAN KEAGAMAAN PESERTA DIDIK MELALUI PROGRAM PALU KANA MAPANDE (PKM) DI KOTA PALU - Andi Anirah (Paedagogia: Jurnal Pendidikan, 2018)
This study discusses the pattern of religious guidance of learners through PKM program, learning interests, and the implications of religious guidance through PKM program in Elementary School Inpres Perumnas Palu Barat. This research is a qualitative descriptive research based on phenomenological approach, that is describing various events and its relation to learners in certain situations. Data collection is done through observation, interview, and documentation. The results showed that the pattern of religious guidance through PKM program in SDN Gugus IV (SD Inpres Perumnas) was greeted enthusiastically by the students. However, the interest of learners in following religious coaching is different, some are very enthusiastic, but some of them not enthusiastic. The implication of religious guidance through PKM program can correct and improve the ability of learners in reading and writing verses of Al Quran. They can also actualize memorization materials, daily prayers, and understand the procedures of worship in daily life.